Discovery and engineering of antimicrobial peptides to combat food spoilage - BECKETT, MICHAEL CHRISTOPHER (Trinity College Dublin. School of Genetics & Microbiology. Discipline of Microbiology, 2019)
This work sought to use a bioinformatics based approach to discover plant derived antimicrobial peptides which were structurally similar to human β-defensin 3 (HBD3) and which possessed effective antimicrobial activity against the food spoiling bacteria Lactobacillus brevis which could be used as food preservatives. This approach identified three candidate peptides, Fabatin, Cp-Thionin and Mungbean defensin PDF-1. The latter was found to have no antimicrobial activity under physiological relevant conditions. The former two were found to have antimicrobial activity but this activity was found to be salt sensitive, thermolabile and was dependent on intramolecular disulfide bond formation. This in vitro analysis also uncovered a direct correlation between antimicrobial activity and cationic charge. This observation was used to rationally design two peptides with increased positive charge based on the inactive Mungbean defensin backbone; 3-Arg and 5-Arg analogue peptides. In vitro analysis revealed that these peptides had increased activity but that increased charge could not overcome the effect of competing salt ions in the assay environment. This activity was also found to be dependent on disulfide bond formation and was thermolabile. A further three peptides with increased structural fluidity were designed based on the 5-Arg analogue peptide backbone; all cysteine knockout, internal cysteine knockout and N-terminal fluid analogue. In vitro analysis revealed that increasing the structural fluidity decreased the antimicrobial activity. This rational design approach was also used to design two peptides with lower molecular weight than the parental 5-Arg analogue peptide; 1-strand deletion and 2-strand deletion analogues. Again in vitro analysis showed that these structural perturbations reduced the antimicrobial activity of the analogue peptides in comparison to the lead molecule. An expression platform, based on the yeast artificial chromosome pYAC4, was designed which could be used for the in situ expression of multiple copies of the genes for the antimicrobial peptides from Saccharomyces pastorianus. It was designed to be stably maintained within the yeast cell without the need for antibiotic selection. Three copies of a recombinant HBD3 expression cassette were cloned into the vector. ELISA analysis showed that there was a somewhat linear relationship between the gene copy number and the level of peptide production. This analysis also showed that the majority of this produced peptide was retained within the cell and was not secreted into the extracellular space. Analysis also showed that the vector was not stably maintained within the cell without the use of antibiotic selective pressure and that this instability directly correlated with the number of copies of the recombinant expression cassette. The genes for the peptides Fabatin, Cp-Thionin and the 3-Arg analogue peptide were synthesised and cloned into the high copy number expression vector pRS42H for the in situ production of the peptides from S. pastorianus. Mass spectrometry analysis showed that the peptides were being produced by the yeast and a qualitative assessment of the data suggested that again the majority of the produced peptide was retained within the yeast cell. In vivo co-culture antimicrobial analysis against Lactobacillus brevis showed that the 3-Arg analogue peptide expression system could reduce the proliferation of the bacteria and that the most effective control was produced when the assay was conducted using brewers wort at 10?C. Over all this work has expanded the repertoire of antimicrobial peptides available for use as food preservatives and that in situ production of these peptides from S. pastorianus could be used to control food spoilage bacteria.
APPROVED
Keywords: Food Spoilage, Antimicrobial Peptides, Defensin, Saccharomyces, Lactobacillus